Transition from illegal regimes under international law - d; ebrary, Inc. (Cambridge ; New York : Cambridge University Press, 2011)
c
Machine generated contents note: Part I. The Law Governing Illegal Territorial Regimes: 1. Introduction; 2. The case studies; 3. The obligation of non-recognition; Part II. Substantive Issues in Transition: 4. Treaty relations of the territory; 5. The status of settlers implanted by the illegal regime; 6. The effect of transition on the internal law of the territory; 7. Land titles granted under the illegal regime; 8. Conclusion: illegality, non-recognition and transition.
Includes bibliographical references and index.
Electronic reproduction.
Keywords: State succession; De facto doctrine; Legitimacy of governments; Regime change; Electronic books